2005
DOI: 10.1590/s0037-86822005000400016
|View full text |Cite
|
Sign up to set email alerts
|

Phlebotomine sandflies in a focus of dermal leishmaniasis in the eastern region of the Brazilian State of Santa Catarina: preliminary results (Diptera: Psychodidae)

Abstract: Due to the occurrence of cases of dermal leishmaniasis in the Municipality of Piçarras, in the East

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 13 publications
3
5
0
3
Order By: Relevance
“…neivai in the city of Teodoro Sampaio. In the city of Piçarras, in the state of Santa Catarina, Marcondes et al (2005) observed the predominance of Ny. neivai in areas with occurrence of ACL.…”
Section: Resultsmentioning
confidence: 95%
“…neivai in the city of Teodoro Sampaio. In the city of Piçarras, in the state of Santa Catarina, Marcondes et al (2005) observed the predominance of Ny. neivai in areas with occurrence of ACL.…”
Section: Resultsmentioning
confidence: 95%
“…Esse fato também foi observado no parque do Ingá, município de Maringá, onde se coletou maior número de N. whitmani em abrigos de onça, aves, mão-pelada, quati, queixada e, em menor número, em outros animais silvestres, sugerindo o ecletismo alimentar da espécie (Teodoro et al 1998(Teodoro et al , 2003a. No município de Piçarras, SC, N. neivai foi a espécie dominante em coletas realizadas nas proximidades de residências de pacientes com LTA (Marcondes et al 2005). Em quatro municípios de Tocantins, N. whitmani foi a espécie mais freqüente e a mais encontrada em coletas realizadas no peridomicílio, que compreendia abrigo de animais domésticos e árvores isoladas ao redor da casa (Andrade Filho et al 2001) (Teodoro et al 2001b(Teodoro et al , 2004.…”
Section: Resultsunclassified
“…In MG, L. fischeri was shown to be among the four species of sand flies with the highest population density in coffee plantations that were in areas of ACL transmission (Alexander et al 2002), while its presence was also recorded in areas of ACL in SC (Marcondes et al 2005).…”
Section: Lutzomyia (Pintomyia) Fischerimentioning
confidence: 97%